Peran Kritis Bank Sentral dalam Menghadapi Gejolak Ekonomi - Muchammad Rizkiansyah Fakhreza; Darian Fahris Ghofur; Rahmad Aditya Eka Febriyanto; Rini Puji Astuti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This research discusses the critical role of central banks in the face of economic turmoil characterized by monetary and financial instability. The background of this research is the importance of central banks as controllers of monetary policy and financial system stability in responding to global and domestic economic crises. The research objective is to analyze the strategic steps of the central bank, especially Bank Indonesia, in maintaining exchange rate stability, controlling inflation, and ensuring the liquidity and health of the banking sector during times of turmoil. The research method used is qualitative with data analysis conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The findings show that the central bank acts as a lender of last resort, intervenes in the foreign exchange market, adjusts the benchmark interest rate, and collaborates with the government and other financial authorities to maintain national economic stability and support economic recovery effectively.